Simulation based study of non-planar multigate indium gallium arsenide quantum well field effect transistors - Haque, Tausif Omar; Shifain, Joyoti; Mallick, Protim; Islam, Md. Rizwanul (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.